Cortistatin inhibits arterial calcification in rats via GSK3β/β‐catenin and protein kinase C signalling but not c‐Jun N‐terminal kinase signalling. (8th March 2018) - Liu, Y.; Lin, F.; Fu, Y.; Chen, W.; Liu, W.; Chi, J.; Zhang, X.; Yin, X.
Abstract: Aim: Cortistatin (CST) is a newly discovered endogenous active peptide that exerts protective effects on the cardiovascular system. However, the relationship between CST and aortic calcification and the underlying mechanism remain obscure. Therefore, we investigated effects of CST on aortic calcification and its signalling pathways. Methods: Calcium content and alkaline phosphatase (ALP) activity were measured using the o‐cresolphthalein colorimetric method and ALP assay kit respectively. Protein expression of smooth muscle (SM)‐ɑ‐actin, osteocalcin (OCN), β‐catenin, glycogen synthase kinase 3β (GSK3β), p‐GSK3β, protein kinase C (PKC), p‐PKC, c‐Jun N‐terminal kinase (JNK) and p‐JNK was determined using Western blotting. Results: In aorta from a rat vitamin D3 calcification model, CST abrogated calcium deposition and pathological damage, decreased the protein expression of OCN and β‐catenin and increased SM‐ɑ‐actin expression. In a rat cultured vascular smooth muscular cell (VSMC) calcification model induced by β‐glycerophosphate (β‐GP), CST inhibited the increase in ALP activity, calcium content and OCN protein and the decrease in SM‐α‐actin expression. CST also inhibited the β‐GP‐induced increase in p‐GSK3β and β‐catenin protein (both P < .05). The inhibitory effects of CST on ALP activity, calcium deposition and β‐catenin protein were abolished by pretreatment with lithium chloride, a GSK3β inhibitor. CST promoted the protein expression of p‐PKC by 68.5% ( P < .01), but not p‐JNK. The ability of CST to attenuate β‐GP‐induced increase in ALP activity, calcium content and OCN expression in the VSMC model was abolished by pretreatment with the PKC inhibitor Go6976. Conclusion: These results indicate that CST inhibits aortic calcification and osteogenic differentiation of VSMCs likely via the GSK3β/β‐catenin and PKC signalling pathways, but not JNK signalling pathway.